Sources of conflicts, conflict resolution strategies, factors considered in and views on marriage of engaged heterosexual young adult pairs in Metro Manila - Sagum, Erika May G.; Reyes, Dannah S.; Simbillo, Lariz Diane A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The study examines the points of view and experiences of engaged heterosexual young adult pairs on conflicts and marriage. It focused on four variables: sources of conflicts, conflict resolution strategies, factors considered in marriage, and views on marriage.The study has shown the different sources of conflicts of engaged young pairs in which time comes in as the top conflict source. The female and males respondents were seen to have similarities and differences when it comes to the sources of conflicts they cited. As individuals, both female and male participants use the three conflict resolution strategies: compromise, avoidance, and attack. Combinations of the conflict resolution strategies were also shown as responses like avoidance and compromise, and avoidance and attack emerged from the participants. All the participants shift to the compromise resolution strategy when facing conflicts as a pair. Some of the factors that the participants considered in marriage were career goals and finances, thinking of family?s welfare of origin, and emotional preparedness. Most of the participants in the study view marriage as a commitment that involves feelings of love. Though females and males have similarities when it comes to their views on marriage, some of the themes that emerged from the responses of the females did not come forward from the answers of the males and vice versa. It is recommended to study not only engaged young pairs but also dating or newly married pairs as the researchers believe that it is highly probable that there would be great shifts on how such pairs view relationship topics like conflicts and marriage.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Marital conflict -- Philippines -- Metro Manila